Specialist service for the provision of opthalmic benefit (circular) - Harwood, E. G.
1929-01 1929 1920s 8 pages The fixed total liability of the Approved Society in respect of each member is 10s. 6d., payable to the Ophthalmic Surgeon for his examination, and a further 7s. 6d. in respect of the glasses where prescribed, representing a minimum liability of 10s. 6d. and a maximum liability of 18s. For this sum the patient will be provided without charge with one of three alternative patterns of frame, including rimless eyeglasses, glazed with lenses of any power ordered by the Ophthalmic Surgeon (with the exception of Crookes' glass, tinted glass, prisms or bifocals) complete with case. For an additional and voluntary payment of 7s. 6d. the member may have the choice of three types of gold filled frame, and for a further 7s. 6d. the whole range of popular forms of eye-wear is available. Details of the frames supplied are furnished in the appendix. For the purpose of maintaining simplicity of administration it is desirable that Societies should adopt the Grade A Schedule, leaving any additional payment for alternative patterns to be made by the member. The promoters however would be prepared to consider applications from individual Approved Societies to adopt the Grade B Schedules as a standard benefit. Where an Approved Society is unable to meet the total cost of any of the three schedules, it is open to it to make a grant towards the cost of the service, the balance being paid by the member. Approved Societies if they adopt this Specialist Service will be providing their members with the best possible ophthalmic treatment carried out by an ophthalmic surgeon who has no pecuniary incentive in prescribing expensive lenses and by an optician who is a specialist dispenser, at fixed charges which will be in operation at all centres and will be prominently displayed for the information of members. In considering the scheme it should be borne in mind that as a result of a thorough and impartial examination of patients by ophthalmic surgeons it is probable that there will be a large number of cases, estimated at from 12%—15% of the total, in which glasses will not be prescribed, the patients being referred to the panel doctor for medical treatment, thereby reducing the liability of the Approved Society in these cases to 10s. 6d. All frames supplied under the scheme are British made and are universal throughout the treatment centres. The lenses are British made but some of the raw material unavoidably is of foreign origin, the percentage of foreign material to the whole being very small. The details of the service have been drawn up by the Association of Dispensing Opticians, Ltd., with the active support and co-operation of the British Medical Association. All medical and optical appointments will be made by the Board on the nomination of a Medical Committee, and the Association of Dispensing Opticians, Ltd. respectively, thus ensuring a highly qualified and efficient personnel. The advantages of securing the services of the members of this Association to carry out the dispensing work in connection with the service should not be over looked. Accurate dispensing is essential to the provision of an efficient ophthalmic treatment service — the inaccurate making up of the prescription or the faulty or careless adjustment of the glasses may do the patient considerable injury. Members of this Association are all highly qualified specialist dispensing opticians who do not practise sight testing, and who devote the whole of their attention to the perfection of the manufacture of lenses and spectacles to give the most efficient results from prescriptions given by ophthalmic surgeons. It should be mentioned, although it does not affect Approved Societies directly, that it has been found possible to extend the benefits of this specialist service to those members of the non-insured population whose economic condition is similar to that of the insured person. As you are possibly aware, this Scheme was drawn up many months ago, but its operation was deferred pending the formulation, under the recent National Health Insurance Act, by the Minister of Health, of regulations governing the administration of ophthalmic benefit. It is possible, however, that some time will elapse before these regulations can come into force, and the promoters have decided therefore to set up the National Ophthalmic Treatment Board without further delay in order to demonstrate the advantages of the ophthalmic service offered under the Scheme. Centres have been established in the towns given in the attached list, and the service will be extended to other areas as occasion demands. 2 292/841.4/1/58